(untitled) (Bangladesh Journal of Medical Science, 2014)
Plantar fasciitis is one of the most common causes of inferior heel pain managed by many physical therapists in variety of clinical settings and wildly treated conservatively. It is usually caused by a biomechanical imbalance resulting in tension along the plantar fascia. It is estimated that 11% to 15% of all foot complaints requiring medical attention can be attributed to this condition. The patient typically presents with inferior heel pain on weight bearing. Pain associated with plantar fasciitis may be throbbing, searing, or piercing, especially with the first few steps in the morning or after periods of inactivity. This article present on overview of the current knowledge on plantar fasciitis and focuses on biomechanics, etiology, diagnosis and treatment strategies, conservative treatment including the physical therapy management are discussed. This information should assist health care practitioners who treat patients with this disorder DOI: http://dx.doi.org/10.3329/bjms.v14i1.17052 Bangladesh Journal of Medical Science Vol.14(1) 2015 p.3-8